The Noel letters [large type] - Evans, Richard Paul (Evans, Richard Paul. Noel collection, 2021)
"After nearly two decades, Noel Post, an editor for a major New York publishing house, returns to her childhood home in Salt Lake City to see her estranged, dying father. What she believed would be a brief visit turns into something more as she inherits the bookstore her father fought to keep alive. Reeling from loneliness, a recent divorce, and unanticipated upheavals in her world, Noel begins receiving letters from an anonymous source, each one containing thoughts and lessons about her life and her future. She begins to reacquaint herself with the bookstore and the people she left behind, and in doing so, starts to unravel the reality of her painful childhood and the truth about her family. As the holidays draw near, she receives a Christmastime revelation that changes not only how she sees the past but also how she views her future"--